Control of the Air‐Sea Oxygen to Heat Flux Ratio During Deep Convection Events. Issue 12 (8th December 2022) - Sun, Daoxun; Ito, Takamitsu; Bracco, Annalisa; Deutsch, Curtis
Abstract: Earth System Models project a decline of dissolved oxygen in the oceans due to climate warming. Observational studies suggest that the ratio of O2 inventory to ocean heat content is several fold larger than what can be explained by solubility alone, but the ratio remains poorly understood. In this work, models of different complexity are used to understand the factors controlling the air‐sea O2 flux to heat flux ratio (O2 /heat flux ratio) during deep convection. Our theoretical analysis based on a one‐dimensional convective adjustment model indicates that the vertical stratification and distribution of oxygen before the convective mixing determines the upper bound for the O2 /heat flux ratio. Two competing rates, the mean entrainment rate of deeper waters into the mixed layer and the rate of air‐sea gas exchange, determine how much the actual ratio departs from the upper bound. The theoretical predictions are tested against the outputs of a regional ocean model. The model sensitivity experiments broadly agree with the theoretical predictions. Our results suggest that the relative vertical gradients of temperature and oxygen at sites of deep water formation are an important local metric to quantify the marginal changes between years with high and lower heat loss. Plain Language Summary: Numerical simulations suggest that the dissolved oxygen (O2 ) in the ocean decreases in a warming climate. An important metric to consider to quantify such decrease is the ratio between the rates of oxygen loss and heat gain, in particular for the high latitude oceans, that ventilate the mid‐depth and deep oceans globally. As the O2 in the deep ocean can only be supplied from the surface during deep mixing events at high latitudes in the cold season, it is important to know how much oxygen can enter the ocean for a given amount of cooling. It will help us estimate how the oceanic oxygen uptake may change if global warming reduces cooling at the ocean surface. This study investigates the ratio between oxygen uptake and cooling during deep winter mixing events using models of different complexities. Our results suggest that this ratio differs under different cooling scenarios. At the convection site, the differences in density and O2 concentration between the surface water and deep water right before the convective season control this ratio. Key Points: A hierarchy of models is used to examine what controls the ratio between air‐sea oxygen flux and heat loss in high latitude oceans The O2 /heat flux ratio of convective events depends on both the surface forcing and background vertical gradients of temperature and O2 The vertical gradients of O2 and temperature are essential for the sensitivity of the oxygen fluxes to changes in heat fluxes